Fabrication of Polystyrene Sulfonate-Chitosan (PSS-Chitosan) Membrane as Dodecyl Benzene Sulfonate (DBS) Adsorbent in Laundry Wastewater - Mandrea Nora; Adyatma Bhagaskara; Virna Agustisari; Alice Lim; Hardian Ridho Alfalah; Dwi Siswanta (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
The combination of polystyrene and chitosan can form polyelectrolyte (PE) membranes. Polystyrene sulfonate-chitosan (PSS-chitosan) adsorbent membrane can adsorb dodecyl benzene sulfonate (DBS) in laundry wastewater. This study aimed to synthesize, identify characteristics, and formulate adsorption effectiveness by PSS-chitosan membranes. The research methods included converting polystyrene into PSS, isolating chitosan, optimizing geometry, making PSS-chitosan membranes, studying adsorption, and applying membranes to laundry wastewater. The resulting membrane was characterized using FTIR and SEM. The results of the infrared spectra showed vibrations of –OH and –NH2 groups at 3418 cm–1, while the SEM image showed a homogeneous membrane surface. The quality of chitosan isolation from shrimp shells was indicated by the degree of deacetylation of 61.3%. The results of the geometry optimization showed the change in the structure’s total energy after adsorption. The PSS-chitosan membrane is resistant to acids but decomposes under alkaline conditions. Optimum adsorption of PSS-chitosan membrane on DBS occurred at pH 8 for 100 minutes. The adsorption kinetics of the PSS-chitosan membrane follows the first pseudo-order equation. PSS-chitosan membrane adsorption isotherm follows the Langmuir isotherm model with an adsorption capacity and efficiency of 3.97 mg.g–1 and 76.6%, respectively, at 0.6 ppm. At the application stage, the PSS-chitosan membrane could adsorb DBS in laundry wastewater by (62.4 ± 7.2) %.